An audit of surgical termination of pregnancy at a level 1 health facility in South Africa - J. Devjee; S. Khedun; J. Moodley (South African Family Practice)
Background: It was alleged that the termination of pregnancy (TOP) services in a certain district health facility were forgoing the opportunity to offer screening tests for human immunodeficiency virus (HIV) and syphilis for women seeking legal medical abortions. In addition, there were concerns regarding the lack of provision of contraceptive services, particularly in view of media reports of young women having repeated TOP procedures as a family planning method. It was therefore decided to perform an audit of the TOP services at this district health facility.